2014
DOI: 10.1016/j.anl.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of TMC1 cause deafness by disrupting mechanoelectrical transduction

Abstract: Objective Mutations of transmembrane channel-like 1 gene (TMC1) can cause dominant (DFNA36) or recessive (DFNB7/B11) deafness. In this article, we describe the characteristics of DFNA36 and DFNB7/B11 deafness, the features of the Tmc1 mutant mouse strains, and recent advances in our understanding of TMC1 function. Methods Publications related to TMC1, DFNA36 or DFNB7/B11 were identified through PubMed. Results All affected DFNA36 subjects showed post-lingual, progressive, sensorineural hearing loss (HL), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 61 publications
(123 reference statements)
1
21
0
Order By: Relevance
“…There are several differences in phenotypes between the DFNA36 families in terms of age of onset and rate of progression. This difference may reflect varied effects of these substitution variants, different genetic backgrounds, or both (Nakanishi, Kurima, Kawashima, & Griffith, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There are several differences in phenotypes between the DFNA36 families in terms of age of onset and rate of progression. This difference may reflect varied effects of these substitution variants, different genetic backgrounds, or both (Nakanishi, Kurima, Kawashima, & Griffith, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…TMC1 has been identified as the responsible gene for both DFNA36 and DFNB7/B11 deafness [ 25 ]. To date, more than 30 TMC1 mutations have been reported to be associated with ARNSHL in families from mostly middle-eastern countries [ 26 ]. In two studies conducted in 93 and 86 patients the frequencies of TMC1 mutations were found to be 4.3% [ 27 ] and 8.1% [ 28 ] respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Cas9 integration in transmembrane channel like 1 (TMC1) TMC1, a transmembrane protein, is required for proper functioning of cochlear hair cells, and has been implicated in hearing loss and prelingual deafness 10 . In mice, this gene is located in chr19 (Accid:NG_008213.1)).…”
Section: Resultsmentioning
confidence: 99%